Exploring Community Attitudes Towards People Labelled as Institutional Child Sex Offenders - Tiffany E. Taylor; Andy Williams (Sexual Offending)
The sexual abuse of children perpetrated by persons who gain access to the child through their roles within child serving institutions, referred to here as institutional child sexual abuse, appears underexplored within the research community despite gaining considerable attention in the media. This study is a preliminary exploration of the stigmatization of individuals labelled as institutional child sexual offenders (ICSO). We recruited 347 community-based participants for an online survey regarding their desired social distance from, and attitudes towards, people labelled as ICSO as compared to those labelled as sexual offenders (SO). We utilized the CATSO, an 18-item attitudinal scale that measures attitudes towards people labelled as sex offenders, and the Bogardus social distance scale which measures the desired level of distance from outgroups. ICSO condition scores were higher than SO scores on the CATSO and lower than SO scores on the Bogardus. Scores for both scales indicate more negative attitudes and increased social desistance towards people labelled as ICSO than towards those labelled as SO. These preliminary findings support the identification of people labelled as ICSO as unique SO subgroup.